(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Understanding and tackling food waste behavior is crucial for achieving Sustainable Development Goal 12, which focuses on responsible consumption and production. It highlights the importance of reducing waste to ensure everyone has enough to eat and to protect the environment. Thus, this study investigates the food waste behavior and awareness among Grade 11 and Grade 12 students of Union Christian College, utilizing a quantitative approach with a descriptive-correlational research design. The researchers gathered data from 139 respondents using adapted survey questionnaires. Weighted mean, standard deviation, and Pearson Product Moment Correlation were the statistical tools used. The findings reveal that respondents showed moderate extent in food wastage, attributing it to large serving portions they receive when buying food. Their food waste behavior is moderately favorable as most of them tend to throw away uneaten food because the food was unappetizing, over-purchasing, over-serving, and spoilage. Meanwhile, they are highly aware of the economic and environmental impact of food wastage, although there is a need to further increase their awareness. Extent of food wastage, food waste behavior, and awareness of impact are all significantly correlated. The findings imply that there is a need to improve the behaviors of the respondents towards food waste leading to better awareness and practice. The researchers recommend focusing on awareness-building programs to induce behavior change through audio-visual material about food waste management. Future research could explore the effectiveness of different educational interventions in reducing food wastage among students.